A 1st–2nd Century CE Assembly Room (Synagogue?) in a Jewish Estate at Tel Rekhesh, Lower Galilee. (2nd January 2019) - Aviam, Mordechai; Kuwabara, Hisao; Hasegawa, Shuichi; Paz, Yitzhak
Abstract : A Jewish farmstead dated to the 1st–2nd centuries CE was discovered during excavations at Tel Rekhesh in the Lower Galilee. In the centre of the western perimeter wall of the structure, a 9-m-square assembly room with an ashlar block bench along the walls was unearthed. It had an entrance in the north and two bases for pillars in the centre to support a flat roof. Given all these features, it has been suggested that the building was a rural synagogue. If correct, this building is one of a small group of synagogues in the Land of Israel that dates to the late Second Temple period. The proximity of Tel Rekhesh to Nazareth offers another perspective to this discovery—an association with Jesus and his ministry in the Galilee.